Strengthening the Role of Laboratories with Authentic Assessment of Student Life Skills - Sri Jumini; Rifqi Muntaqo; Winarto Winarto; Yatim Md Nadrah; Hamzah Hamzah (STAI Hubbulwathan Duri, 2024)
The practicum experience in laboratory settings plays a pivotal role in cultivating essential life skills among students. This study investigates the efficacy of laboratory-based practicums in fostering students' life skills through the utilization of authentic assessment methods. Employing a pre-experimental approach with a one-shot case study design, the research focuses on 5th-semester Physics students engaged in practicum activities, totaling 26 participants. Purposive sampling was employed to determine the research sample. Data collection involved observation techniques, life skills questionnaires, and interviews to evaluate laboratory utilization. Descriptive statistics were employed for data analysis. Findings reveal that practicum-based authentic assessments yield commendable results in students' life skills development, with an average score of 3.73, indicating proficiency. The practicum experience in the laboratory setting facilitates the cultivation of these skills, positioning students to excel in the contemporary industrial landscape characterized by technological advancements. Beyond mere swiftness, individuals in this era must possess adaptable life skills to effectively fulfill their responsibilities, confront challenges with confidence, and adeptly resolve encountered issues.